Text independent emotion recognition for Telugu speech by using prosodic features - Mannepalli, Kasiprasad; Maloji, Suman; Narahari Sastry, Panyam; Danthala, Swetha; Mannepalli, Durgaprasad (International Journal of Engineering and Technology, 2018)
The human speech delivers different types of information about the speaker and speech. From the speech production side, the speech signal carries linguistic information such as the meaningful message and the language and emotional, geographical and the speakerâ€™s physiological characteristics of the speaker information are conveyed. This paper focuses on automatically identifying the emotion of a speaker given a sample of speech. the speech signals considered in this work are collected from Telugu speakers. The features like pitch, pitch related prosody, energy and formants. The overall recognition accuracy obtained is 72% in this work.Â